Ecos de práticas docentes significativas no processo identitário de alunos da EJA - Cangi, Maria Cecilia Orlandi (2024)
This study, with a qualitative approach, used oral reports from students from a private institution to identify, from the student's perspective, the significant formative marks in the context of EJA. To this end, specific objectives were set to verify the student's formative marks from childhood until their return to school, analyze the identity movements that occurred during their school career and seek evidence of significant teaching practices in their school career and in their development process. identity constitution upon returning to school. By structuring the investigation of formative experiences from the perspective of the Youth and Adult Education student, in order to consider their subjectivity in the face of experiences lived at school, the consolidation of this study took place in the approach of qualitative research inspired by autobiographical narratives from starting from open questions, linked to the specific objectives of the research. The participants in this investigation were four EJA high school students from a private school previously selected in an initial activity, which sought to ascertain the meaning attributed by the students to their return to school. The sociologist Dubar (2005, 2009) was used as a theoretical reference for the analysis of the information produced in the interviews, based on his contributions regarding identity processes, the conception of liberating education defended by Freire (1982, 2022) and the constitution of subject based on interpersonal relationships with others proclaimed by Wallon (1986). Bearing in mind the importance of the training of Youth and Adult Education teachers being integrated with the inherent specificities of their target audience, this study brought evidence of significant practices carried out by the teacher, providing a deeper reflection on their performance in this educational segment and bringing contributions to studies on the training of this professional